The role of wind-solar hybrid plants in mitigating renewable energy-droughts - Gangopadhyay,A; Seshadri,AK; Sparks,NJ; Toumi,R (Renewable Energy, 2022)
Increasing the share of weather-dependent renewables in the electricity grid is essential to deeply decarbonize the electricity system. Wind and solar “droughts” or low generation days can severely impact grid stability in a renewable-rich grid. This paper analyzes for the first time wind, solar, and hybrid energy-droughts in India using a stochastic weather generator. Available literature analyze the observational data that is of limited duration (30–40 years). Therefore, discussion of low-probability high-impact renewable energy-droughts that have long return periods (in the range of 30 years) is limited in the literature. The present study seeks to address this research gap by exploring the risk of wind, solar, and wind-solar powered energy-droughts based on simulated long time series (5000 years). It is found that the weather generator captures mean, seasonality, and correlation between wind speed and solar irradiance and is therefore used to estimate return periods of extreme wind and solar-droughts. Our analysis shows that wind-droughts are more intense than solar-droughts in India. We examine the role that wind-solar hybridization can play in offsetting low wind energy episodes. The benefits of hybridization are regionally dependent. In South India, hybrid plants have advantages over either wind or solar plants alone. In comparison, for Rajasthan, the benefits of hybridization are limited. When one of the regions (South India or Rajasthan) has a renewable drought, the other region has only a 10% probability of having a similar drought. Our findings highlight the need for having robust inter-regional grid connections to mitigate regional level renewable droughts.